MELANKOLIA - Rizki Pratama; Erfan Lubis; Irdhan Epria Darma Putra (SENDRATASIK UNP, 2014)
Abstract People could not evade problems when they were doing their daily life routines. These problems made them feel sad, confused and depressed which later led them to what is called as Melancholia. This melancholic feeling surely interrupted them in doing their routines so that it was difficult for them to obtain their life goals. This melancholia phenomenon was then transferred into a music composition. The melancholic feeling would be best felt through a masterpiece of music. It was hoped that by listening to it, people would feel how it was to be melancholic. Kata kunci : Melankolia